A Estética Publicitária: uma linguagem artística e imagética - Amato, Leonardo (2021)
This article implies about the links that take place between the artistic field and the communicational. Based on the principle of advancing techniques until the meeting with the current digital world. As a result, sociocultural changes and changes in capitalists, in order to measure the procedural impacts triggered in the direction of the conception arts and advertising operations. What causes us to explore the consumer industry and respectively the capture of artistic aesthetics navigating all capital layers. In short, clarifying the hypermodern times and their complexity of assimilating in a context given largely by images, the difference between the advertising and the artistic core. Summarizing in question, the promotion of a substantial sum, in which art and advertising often become the same material.